2017
DOI: 10.3390/brainsci7010011
|View full text |Cite
|
Sign up to set email alerts
|

Overview of Traumatic Brain Injury: An Immunological Context

Abstract: Traumatic brain injury (TBI) afflicts people of all ages and genders, and the severity of injury ranges from concussion/mild TBI to severe TBI. Across all spectrums, TBI has wide-ranging, and variable symptomology and outcomes. Treatment options are lacking for the early neuropathology associated with TBIs and for the chronic neuropathological and neurobehavioral deficits. Inflammation and neuroinflammation appear to be major mediators of TBI outcomes. These systems are being intensively studies using animal m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
76
0
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(82 citation statements)
references
References 193 publications
(251 reference statements)
3
76
0
3
Order By: Relevance
“…When exposed to DAMPs, phagocytic microglia are rapidly activated to clear debris (for example, a hematoma), seal defective barriers and produce neurotrophic factors 105107 . However, microglia are also critical for an extensive and often sustainable (up to years) generation of cytokines (for example, IL-1β and IL-6) and ROS, which in turn recruit neutrophils and blood monocytes-macrophages to the injured area 103,105,108 . Furthermore, complement 109 or lysophosphatidylcholine activates inflammasomes in microglia or astrocytes soon after TBI and during neuro-inflammation 110 .…”
Section: Cerebral and Extracerebral Challenges To The Innate Immune Smentioning
confidence: 99%
“…When exposed to DAMPs, phagocytic microglia are rapidly activated to clear debris (for example, a hematoma), seal defective barriers and produce neurotrophic factors 105107 . However, microglia are also critical for an extensive and often sustainable (up to years) generation of cytokines (for example, IL-1β and IL-6) and ROS, which in turn recruit neutrophils and blood monocytes-macrophages to the injured area 103,105,108 . Furthermore, complement 109 or lysophosphatidylcholine activates inflammasomes in microglia or astrocytes soon after TBI and during neuro-inflammation 110 .…”
Section: Cerebral and Extracerebral Challenges To The Innate Immune Smentioning
confidence: 99%
“…TBI is defined as a serious public health problem that disrupts the normal function of the brain and can be caused by a bump, blow or jolt to the head, rapid acceleration and deceleration of the calvarium, or a penetrating head injury 37. There are certain experiments have shown that TBI usually led to brain edema, tissue loss, neurocognitive impairments, and dysfunction of the CNS 38.…”
Section: Roles Of H2s In Brain Diseasesmentioning
confidence: 99%
“…Previous studies have shown that delayed injury is consistently marked by microglial activation and is mediated by inflammatory processes after TBI. 25,26,27 Behaviorally, adolescent TBI animals had lower locomotor velocity shortly after TBI and were no longer distinguishable from controls by 16 DPI. Both adult and adolescent sham and TBI animals increased center time from 4 DPI to 16 DPI.…”
Section: Discussionmentioning
confidence: 99%